Enabling Delay of Gratification Behavior in Those Not So Predisposed: The Moderating Role of Social Support - Liu, Xiaoyan; Wang, Lei; Liao, Jiangqun (Frontiers in Psychology, 2016)
The presence of delay of gratification (DG) in childhood is correlated with success later in a person’s life. Is there any way of helping adults with a low level of DG to obtain similar success? The present research examines how social support helps those low in DG nonetheless to act similarly to those high in DG. This research includes both correlational studies and experiments that manipulate social support as well as both field studies and a laboratory study. The results show that with high social support, employees (Study 1) and university students (Study 2) low in DG report vocational and academic DG behavioral intentions, respectively, similar to those high in DG. Study 3 found that participants low in DG who were primed with high social support expressed job-choice DG similar to those high in the DG. Study 4 controlled for mood and self-image and found that participants low in DG who were primed with high social support expressed more money-choice DG than those high in the DG. Study 5 showed that social support moderated the relationship between DG and actual DG behaviors. These findings provide evidence for a moderating role of social support in the expression of DG behavior.